An observational and theoretical study of the longitudinal variation in neutral temperature induced by aurora heating in the lower thermosphere. Issue 11 (25th November 2013) - Xu, Jiyao; Smith, A. K.; Wang, Wenbin; Jiang, Guoying; Yuan, Wei; Gao, Hong; Yue, Jia; Funke, B.; López‐Puertas, M.; Russell, James M.
Abstract [1] In this paper, observations by thermosphere, ionosphere, mesosphere energetics and dynamics/Sounding of the Atmosphere using Broadband Emission Radiometry from 2002 to 2012 and by Envisat/Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) from 2008 to 2009 are used to study the longitudinal structure of temperature in the lower thermosphere. In order to remove the longitudinal structure induced by tides, diurnally averaged SABER temperatures are used. For MIPAS data, we use averaged temperatures between day and night. The satellite observations show that there are strong longitudinal variations in temperature in the high‐latitude lower thermosphere that persist over all seasons. The peak of the diurnally averaged temperature in the lower thermosphere always occurs around the auroral zone. A clear asymmetry between the two hemispheres in the longitudinal temperature structure is observed, being more pronounced in the Southern than in the Northern Hemisphere. In both hemispheres, the longitudinal variation is dominated by the first harmonic in longitude. The total radiative cooling observed by SABER has a structure in longitude that is similar to that of temperature. Modeling simulations using the Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model reproduce similar features of the longitudinal variations of temperature in the lower thermosphere. Comparison of two model runs with and without auroral heating confirms that auroral heating causes the observed longitudinal variations. The multiyear averaged vertical structures of temperature observed by the two satellite instruments indicate that the impact of auroral heating on the thermodynamics of the neutral atmosphere can penetrate down to about 105 km.